DAMPAK TRANSFER PEMERINTAH TERHADAP POLA PENGELUARAN KONSUMSI RUMAH TANGGA DI INDONESIA - Octavia Muslira; Doni Satria (Universitas Negeri Padang, 2025)
This study aims to analyze the effect of the family Hope Program (PKH) as from of government social assistance on household consumption expenditure patterns in Indonesia. The approach used is the Quadratic Almost Ideal System (QUAIDS) with the Three-Stage Least Squares (3SLS) estimation technique, using the 2020 National Socio-Economic Survey (SUSENAS) data. The estimation results show that government assistance encourages a crowding in effect in the structure of household consumption, which is reflected in an increase in the proportion of expenditure on categories such as food, education, lighting fuel, and other expenditures. This effect indicates that social assistance acts as an instrument that strengthens the purchasing power of poor households while allowing budget reallocation to priority sectors that were previously neglected. In contrast, the proportion of expenditure on commodities that are flexible or can be postponed, such as transportation, durable goods, entertainment, and clothing, tends to decrease. These findings reinforce the role of social assistance programs in increasing welfare and improving the quality of consumption of vulnerable households.